Position Control Strategies Of Dc Servo Motor - Alwi, Erni Aznida (2003)
Direct Current (DC) servo motor is mainly studied for its speed and position control. This study however, concentrated only on the position control part. The technology of position control of DC servo motor has evolved considerably over the past few years. To date, various types of DC servo motor position control scheme have been developed. To name some, there are microcontroller-based control, PC based control, adaptive control and optimal control. In this study, a simulation and a real time implementation of DC servo motor position control are presented. The types of controller designed and tested are the proportional integral derivative (PID) controller and the adaptive controller. PID control scheme is chosen mainly because of its simplicity advantage while the adaptive scheme is chosen due to its ability to adapt.With some modification and adaptation, these two designed schemes have been interfaced via MATLAB Real Time Toolbox to a servo trainer as the plant for real time implementation. This toolbox contains a library of blocks with real time input and output support. Following the design part, the modeling and simulation part are done. The mathematical design or model of the controller then has been simulated in MATLAB before being interfaced to the real plant. The PID and adaptive controller have been successfully implemented to the plant with satisfactory results. Analysis has been done to compare the performance of the two controllers from the simulation and real time results.